TeraHertz desorption emission spectroscopy (THz DES) of space relevant ices. Issue 2 (25th July 2022) - Auriacombe, Olivier; Rea, S; Ioppolo, S; Oldfield, M; Parkes, S; Ellison, B; Fraser, H J
ABSTRACT: We present an experimental instrument that performs laboratory-based gas-phase Terahertz Desorption Emission Spectroscopy (THz-DES) experiments in support of astrochemistry. The measurement system combines a terahertz heterodyne radiometer that uses room temperature semiconductor mixer diode technology previously developed for the purposes of Earth observation, with a high-vacuum desorption gas cell and high-speed digital sampling circuitry to enable high spectral and temporal resolution spectroscopy of molecular species with thermal discrimination. During use, molecules are condensed on to a liquid nitrogen cooled metal finger to emulate ice structures that may be present in space. Following deposition, thermal desorption is controlled and initiated by means of a heater and monitored via a temperature sensor. The 'rest frequency' spectral signatures of molecules released into the vacuum cell environment are detected by the heterodyne radiometer in real-time and characterized with high spectral resolution. To demonstrate the viability of the instrument, we have studied Nitrous Oxide (N2 O). This molecule strongly emits within the terahertz (sub-millimetre wavelength) range and provide a suitable test gas and we compare the results obtained with more traditional techniques such as quadrupole mass spectrometry. The results obtained allow us to fully characterize the measurement method and we discuss its potential use as a laboratory tool in support of astrochemical observations of molecular species in the interstellar medium and the Solar System.